2018
DOI: 10.1093/mnras/sty2391
|View full text |Cite
|
Sign up to set email alerts
|

Why do many early-type galaxies lack emission lines? I. Fossil clues

Abstract: Early-type retired galaxies (RGs, i.e. galaxies which no longer form stars) can be divided into two classes: those with no emission lines, here dubbed lineless RGs, and those with emission lines, dubbed liny RGs. Both types of galaxies contain hot lowmass evolved stars (HOLMES) which emit ionizing photons. The difference must thus lie in the presence or absence of a reservoir of ionizable gas. From a volume-limited sample of 38 038 elliptical galaxies, we explore differences in physical properties between liny… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 124 publications
(159 reference statements)
1
32
0
Order By: Relevance
“…7 are comparable to the ones of In the top panel, we plot only galaxies with S/N > 3 in Hα, while in the bottom panel we exclude 3 galaxies for which there is no WISE data. Herpich et al (2018), who find that, at all stellar masses, ETGs with emission lines have larger A V and redder W2−W3 when compared to ETGs without emission lines. We have shown that ETGs with young components have more ionised gas than other ETGs; however, the source of this ionisation is not clear.…”
Section: The Ism Of Etgs With Young Componentsmentioning
confidence: 98%
See 2 more Smart Citations
“…7 are comparable to the ones of In the top panel, we plot only galaxies with S/N > 3 in Hα, while in the bottom panel we exclude 3 galaxies for which there is no WISE data. Herpich et al (2018), who find that, at all stellar masses, ETGs with emission lines have larger A V and redder W2−W3 when compared to ETGs without emission lines. We have shown that ETGs with young components have more ionised gas than other ETGs; however, the source of this ionisation is not clear.…”
Section: The Ism Of Etgs With Young Componentsmentioning
confidence: 98%
“…The molecular gas fractions are found to be related to both star-formation histories (Young et al 2014) and kinematics (Cappellari et al 2013), in that galaxies with rotating stellar disks have larger gas fractions. Ionised gas can also be detected in the ISM of ETGs of all masses (Herpich et al 2018). In this section, we will investigate the connection between the presence or absence of young components and the ISM properties of ETGs.…”
Section: The Ism Of Etgs With Young Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…with its classes, according to the description by Cid Fernandes et al (2011), which in brief segragates galaxies into 5 groups: star-forming (SF), strong and weak AGN (sAGN and wAGN), retired galaxies (RG), and passive (lineless) galaxies, as follows: Differently from the BPT chart, WHAN enables us to spot the retired and some of the passive population, which is suitable for this investigation. Additionally, a number of objects cannot be detected in neither of them, mostly due to the simple fact that our sample is focused on RSGs, hence including a sizeable amount of lineless galaxies (Herpich et al 2018); nevertheless, this does not guarantee that all of these objects are, in fact, quiescent, for they can be unclassified due to other unknown issues (e.g. low S/N) -these systems are tagged as 'unclassified'.…”
Section: Uv Bright Rsgs and Their Emission-linesmentioning
confidence: 98%
“…The presence of AGN could also contribute to the UV flux (e.g. Cid Fernandes et al 2000;Heinis et al 2016;Padovani et al 2017) in red-sequence galaxies (RSGs); those are often classified as low-ionisation nuclear emission-line region (LINERs): their ionisation mechanisms are historically attributed to AGN activity -which has been strongly questioned, for many of such galaxies seem to be ionised by hot low-mass evolved (post-main sequence) stars (AKA HOLMES, Cid Fernandes et al 2011;Singh et al 2013;Belfiore et al 2016;Padovani et al 2017;Herpich et al 2018). On the other hand, it seems that AGN activity contributes only to a tiny part of the far-UV emission in systems with very bright nuclei (e.g.…”
Section: Introductionmentioning
confidence: 99%